Tugas Pramuwisata dalam Meeting Service - I Ketut Arta Widana (UHN IGB Sugriwa Denpasar, 2017)
Tourists guide, for common people, is mainly known as a person who escort tourists to tourist objects. Only a few people, specially those who works for travel industries, know that a tourist guide has several jobs to do, from picking up clients at the airport, transfering to different hotels, escorting back to the departure terminal, and also conducting meeting service that includesolving problems and selling optional tours. Meeting service plays important role in increasing economic benefit both for the travel agent and also for the tourists guide as a representative. It also helps the customers in achieving customers’ satisfaction through problem solving, hotel and resort presentation and tour organizaton. This article gives technical knowledge to improve skillas a representative of the company and suficient understanding of the job description as a tourists guide during the meeting service after the clients’ arrival